Maximizing Students’ Vocabulary Mastery by Using Liveworksheet Apps - Melyna Hariana Wati; Sugeng Hardi; Teguh Sulistyo; Melyna Hariana Wati; Sugeng Hardi (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2023)
This class action research focuses on maximizing vocabulary mastery in 7th grade, especially in the 7H class at SMPN 1 Papar Kediri. In this class action research involves technology-based media, namely liveworksheet apps. With the help of this application, it is hoped that teachers can increase children's interest in learning English because by using this application formative or summative assessments can be formed in a game. The researchers used one of the game features, namely drag-drop. The major instrument used was a test to measure the students’ vocabulary mastery. Also, it applied an interview to evaluate students’ opinions about the application. The results obtained are that the majority of students claim to be happy to use this media because they are considered easy and as many as 75 percent of the total students in one class get results, namely their grades improve